Fe-embedded ZIF-derived N-doped carbon nanoparticles for enhanced selective reduction of p-nitrophenol. Issue 2 (April 2023) - Yu, Weiting; Qiu, Leben; Zhu, Jieyun; Chen, Sizhuo; Song, Shuang
Abstract: The selective catalytic reduction of nitroaromatics towards aromatic amines under mild reaction condition is an important approach to reduce the toxicity of waste effluents from industry and afterwards utilize the product as important fine organic chemical raw materials. P-nitrophenol (PNP) is chosen as the probe molecule of nitroaromatics in this study. A Fe-embedded N-doped Carbon (Fe-N-C) catalyst prepared using ZIF-8 has been identified as a highly active, selective and stable catalyst in the selective catalytic reduction of PNP. The Fe-N-C catalyst is for the first time applied in PNP reduction and found to present 100% conversion and 100% product selectivity. A mechanism investigation has been carried out to conclude that in the PNP reduction on Fe-N-C, water acts as the main hydrogen provider and sodium borohydride is the electron donator. Furthermore, the Fe-N-C catalyst works well when it is applied in PNP degradation in real water samples, which further indicates its applicability in industrial wastewater treatment. This work offers a simple and useful strategy to design robust catalysts for the selective catalytic reduction of nitroaromatics. Graphical Abstract: ga1 Highlights: Fe-N-C is highly active, selective, and stable in p-nitrophenol reduction. An isotope experiment has been designed to reveal the reaction mechanism. Fe-N-C is still robust for p-nitrophenol degradation in real water treatment.